The effect of cryomechanodestruction on activation of heteropolysaccaride-protein nanocomplexes when developing nanotechnologies of plant supplements - Pavlyuk, Raisa; Pogarska, Viktoriya; Balabai, Katerina; Pavlyuk, Vadim; Kotuyk, Тatyana (Eastern-European Journal of Enterprise Technologies, 2016)
The regularities and mechanisms of the effect of deep processing of plant raw materials were established, such as finely dispersed grinding in developing nanotechnology of obtaining frozen nanopuree and nanopowders on the transformation of bound amino acids of protein to free soluble form by меchanolysis of molecules of protein (by 45…55 % to separate αamino acids). We discovered the mechanism of mechanodestruction of protein molecules and its nanocomplexes with other biopolymers and BAS, which is linked to mechanocracking. In the deep processing of plant raw materials, in particular, Jerusalem artichoke, which is based on the comprehensive action of cryogenic «shock» freezing, freeze drying and finely dispersed grinding processes when obtaining nanopowders, the processes of cryodestruction, mechanodestruction and mechanochemistry occur that lead to the fuller extraction of BAS from the raw material (by 1.8…2.3 times more than is in the original raw material) and destruction of biopolymers (inulin, proteins) to their monomers. It was found that the freezing and cryomechanodestruction lead to the transformation of chemical substances of Jerusalem artichoke (cryomechanochemistry) and transformation, in particular, conformational changes of protein molecules: reduction of radius of the volume of a protein molecule, radius of its nucleus, and also to a decrease in the indicator of filling the nucleaus with hydrophobic remains of amino acids. In addition, the shape of protein molecules changes. We proposed and designed cryogenic nanotechnology of finely dispersed frozen nanopuree and nanopowders from Jerusalem artichoke with prebiotic properties. It was shown that nanosupplements exceed the known world analogues in the content of BAS and dispersed composition. In addition, a large part of the substances (both BAS and biopolymers) is in the nanodimensional form.